O ensino da leitura e interpretação de texto com tirinhas através da gamificação - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work aims to contribute to the Portuguese language classes focused on teaching reading and text interpretation through the development of an educational product through a sequence of playful activities, which aims to use comic strips through the active methodology of gamification. The theoretical framework that supports this course completion work is divided into three parts that articulate with each other: Reading and interpretation (LEFFA, 1996; KOCH, 2003; ANTUNES, 2009); Textual genres (BAKHTIN, 1997, 2000; MARCUSCHI, 2008) and Gamification (FARDO, 2013; MORAN, 2018). The educational product was elaborated and analyzed based on an evaluation rubric, elaborated by the author of the paper, based on the ARCS Model (1983) and the BNCC guidelines. From the analysis of the educational product it was possible to verify the potential of using gamification in the production of materials for Portuguese language classes, focused on reading and text interpretation. Furthermore, we concluded that when reading is worked in an interdisciplinary way with resources and themes that are integrated into the student's social environment, the opportunities to develop the student's reading and interpretation competence are increased.
Teaching reading and text interpretation with comic strips through gamification
Keywords: Tirinhas; Gamificação; Leitura; Interpretação de texto; Comic strips; Gamification; Reading; Text interpretation; CNPQ::CIENCIAS SOCIAIS APLICADAS